8X-(3X+6)=4-X

Simple and best practice solution for 8X-(3X+6)=4-X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8X-(3X+6)=4-X equation:


Simplifying
8X + -1(3X + 6) = 4 + -1X

Reorder the terms:
8X + -1(6 + 3X) = 4 + -1X
8X + (6 * -1 + 3X * -1) = 4 + -1X
8X + (-6 + -3X) = 4 + -1X

Reorder the terms:
-6 + 8X + -3X = 4 + -1X

Combine like terms: 8X + -3X = 5X
-6 + 5X = 4 + -1X

Solving
-6 + 5X = 4 + -1X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add 'X' to each side of the equation.
-6 + 5X + X = 4 + -1X + X

Combine like terms: 5X + X = 6X
-6 + 6X = 4 + -1X + X

Combine like terms: -1X + X = 0
-6 + 6X = 4 + 0
-6 + 6X = 4

Add '6' to each side of the equation.
-6 + 6 + 6X = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 6X = 4 + 6
6X = 4 + 6

Combine like terms: 4 + 6 = 10
6X = 10

Divide each side by '6'.
X = 1.666666667

Simplifying
X = 1.666666667

See similar equations:

| x-(8-3)=x-11 | | 1/3m=5 | | 3x=61.50 | | 9-(7k-2)+2k=4(k+3)+5 | | 5k+10=2k+7 | | 12(6-1/2) | | 10=x/7 | | 12d-16/6 | | 12x-8x-75=29 | | -9=4(x-3)-7x | | 1/2b-8=10-2b | | 1.5r+15=2.25 | | 5+(-8)=-3x+7 | | x-5=53 | | 4x^3+6x-44=0 | | 3x-xy=20fory | | 8+12n+72=9 | | 24f+15/9 | | 53/5=x | | x+3=3x+6 | | 53=3x+8 | | 7x+-140=56 | | 18x+9=9x+18 | | 53-5=x | | 8+7z/11 | | 5(2x+3)+4(x-7)= | | (3x+2)+11=(22-x)+11 | | -3(-4-2n)=36 | | G=5/2-21 | | 5(.75)-2y=-9 | | 2.99=19.99+1.99 | | 180-148= |

Equations solver categories